GE_GERICHTE P/7305/2021 vom 22. Dezember 2023 - GE Cour de justice (2023)
CLASSEMENT DE LA PROCÉDURE;MISE EN ACCUSATION;NE BIS IN IDEM;USURE(DROIT PÉNAL);TRAITE D'ÊTRES HUMAINS | CPP.16; CPP.319; CPP.325; CP.157; CP.182